2012
DOI: 10.1021/ac2024975
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free and Substrate-Free Potentiometric Aptasensing Using Polycation-Sensitive Membrane Electrodes

Abstract: A potentiometric label-free and substrate-free (LFSF) aptasensing strategy which eliminates the labeling, separation, and immobilization steps is described in this paper. An aptamer binds specifically to a target molecule via reaction incubation, which could induce a change in the aptamer conformation from a random coil-like configuration to a rigid folded structure. Such a target binding-induced aptamer conformational change effectively prevents the aptamer from electrostatically interacting with the protamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…This effect may be due to the fact that the protamine molecules with high molecular weights need a rather long time to cross the membrane [13]. Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33].…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be due to the fact that the protamine molecules with high molecular weights need a rather long time to cross the membrane [13]. Recently, it has been found that the ion fluxes across the membrane can be modulated and controlled precisely by applying an external current [23,[30][31][32]. Previous reports have shown that ions across the polymeric membrane ion-selective electrode can be selectively and precisely delivered to the sample solution for calibration-free titrations [33].…”
Section: Resultsmentioning
confidence: 99%
“…1A). The procedures for switching between the galvanostatic and potentiostatic steps were designed as described before [22,23]. The opencircuit potential of the electrode was first recorded for 1 s (pulse 1).…”
Section: Methodsmentioning
confidence: 99%
“…1A shows that the current-dependent potential decreases with increasing the concentration of trypsin in the sample solution, which is due to the decrease of the concentration of free protamine released at the sample-membrane interface via the degradation by trypsin. As described before [18,22], the consumption of protamine would facilitate the stripping of protamine out of the membrane surface via the ion-exchange process with sodium ions from the sample solution, which can dramatically decrease the potential values. Fig.…”
Section: Analytical Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, potentiometry based on ion-selective electrodes (ISEs) have evolved to provide a promising transducer for biosensing [22][23][24][25][26]. Typically, these electrodes have been extensively investigated for biosensing via zero-current potentiometry.…”
Section: Introductionmentioning
confidence: 99%